Patronate and Patronage in Early and Classical Islam - Bernards, Monique,; Nawas, John, (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This book deals with patronate and patronage ( walā' ) of early and classical Islam. Though Webster's Third has the term "mawla," the concept remains very difficult to come to grips with. Fourteen contributions by renowned scholars analyze the social and cultural phenomenon of walā' from various angles. As a whole, the book conveys what we presently know about patronate and patronage during the first four centuries of Islam. Inasmuch as the contributors have used different methods - from a close rereading of primary sources to the application of social theory and quantitative analysis - the book additionally offers an overview of methodologies current in the field of Islamic Studies.